Grande Distribuzione Organizzata e agromafie: lo sfruttamento degli immigrati regolari e la funzione dei criminal hubs - Fanizza, Fiammetta (SocietàMutamentoPolitica, 2020)
The focus of this articles is the link between massive market retail and criminal business. It argues about the agromafia’s involvement in the agriculture activities and, in general, in the food markets productions. Thanks to many police investigations, it’s possible to assert that agromafia is mainly based on immigrant exploitation. In particular, the illegal forms of labourer hiring allow agromafia to develop more and more trades both in Italy and in Europe.